Functional and Biological Role of Endothelial Precursor Cells in Tumour Progression: A New Potential Therapeutic Target in Haematological Malignancies. (14th December 2015) - Reale, Antonia; Melaccio, Assunta; Lamanuzzi, Aurelia; Saltarella, Ilaria; Dammacco, Franco; Vacca, Angelo; Ria, Roberto
Abstract : It was believed that vasculogenesis occurred only during embryo life and that postnatal formation of vessels arose from angiogenesis. Recent findings demonstrate the existence of Endothelial Precursor Cells (EPCs), which take partin postnatal vasculogenesis. EPCs are recruited from the bone marrow under the stimulation of growth factors and cytokines and reach the sites of neovascularization in both physiological and pathological conditions such as malignancies where they contribute to the "angiogenic switch" and tumor progression. An implementation of circulating EPCs in the bloodstream of patients with haematological malignancies has been demonstrated. This increase is strictly related to the bone marrow microvessel density and correlated with a poor prognosis. The EPCs characterization is a very complex process and still under investigation. This literature review aims to provide an overview of the functional and biological role of EPCs in haematological malignancies and to investigate their potential as a new cancer therapeutic target.